2007
DOI: 10.1074/jbc.m707915200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Mediates Necrotic Cell Swelling in SN4741 Dopaminergic Neurons through P2X7 Receptors

Abstract: Extracellular ATP has recently been identified as an important regulator of cell death in response to pathological insults. When SN4741 cells, which are dopaminergic neurons derived from the substantia nigra of transgenic mouse embryos, are exposed to ATP, cell death occurs. This cell death is associated with prominent cell swelling, loss of ER integrity, the formation of many large cytoplasmic vacuoles, and subsequent cytolysis and DNA release. In addition, the cleavage of caspase-3, a hallmark of apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 54 publications
9
60
0
3
Order By: Relevance
“…This finding agrees with our previous study on the receptor expression in other PDAC cell lines,24 and with several studies performed on different cancer types, e.g., breast cancer, nonsmall cell lung cancer35 and melanoma 36. In our study, stimulation of PancTu‐1 Luc with increasing exogenous concentrations of ATP or BzATP decreased cell proliferation/survival, similar to other PDAC cell lines and reports on other cancer cells 24, 29, 37. The allosteric inhibitor of P2X7R, AZ10606120, significantly reduced BrdU incorporation, due to an arrest of cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with our previous study on the receptor expression in other PDAC cell lines,24 and with several studies performed on different cancer types, e.g., breast cancer, nonsmall cell lung cancer35 and melanoma 36. In our study, stimulation of PancTu‐1 Luc with increasing exogenous concentrations of ATP or BzATP decreased cell proliferation/survival, similar to other PDAC cell lines and reports on other cancer cells 24, 29, 37. The allosteric inhibitor of P2X7R, AZ10606120, significantly reduced BrdU incorporation, due to an arrest of cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, nucleotides released after brain insults have been proposed as danger signals that display dual functions, first alerting tissue to trigger protective responses against damage, and then, upon sustained release and activation, can function as amplifiers to augment inflammation and toxicity. Focusing on P2X 7 receptors, sustained activation seems to be coupled to cell death, as was first reported in cells of blood lineage (Surprenant et al 1996;Di Virgilio 1999) and also in some neuronal and glial cells, such as cortical, dopaminergic neurons and cortical astrocytes (Fumagalli et al 2004;Kong et al 2005;Jun et al 2007). However, P2X 7 is not associated to cell death in other cells, such as cerebellar astrocytes (Delicado et al 2005), suggesting that the heterogeneity observed in P2X 7 -mediated actions can be cell and tissue specific and can depend on differences at P2X 7 receptor expression levels.…”
Section: Discussionmentioning
confidence: 98%
“…mRNA (1.5 g) was converted to cDNA by using reverse transcriptase (Reverse Transcriptase Systems; Promega, Madison, WI) according to the supplied protocol. A fixed volume of each sample cDNA was added to a Taq polymerase master mix (Promega), along with 5 M concentrations of the forward and reverse primers for bovine P2X 7 or ␤-actin. Primers were designed by performing a PubMed (National Center for Biotechnology Information, Bethesda, MD) search for coding sequences for these bovine genes.…”
Section: Methodsmentioning
confidence: 99%